Larval development of the pedunculate barnacles Octolasmis angulata Aurivillius 1894 and Octolasmis cor Aurivillius 1892 (Cirripedia: Thoracica: Poecilasmatidae) from the gills of the mud crab, Scylla tranquebarica Fabricius, 1798 - Yap, F.C.; Wong, W.L.; Maule, A.G.; Brennan, G.P.; Lim, S.L.H. (Elsevier, 2015)
Detailed studies of larval development of Octolasmis angulata and Octolasmis cor are pivotal in understanding the larval morphological evolution as well as enhancing the functional ecology. Six planktotrophic naupliar stages and one non-feeding cyprid stage are documented in details for the first time for the two species of Octolasmis. Morphologically, the larvae of O.angulata and O.cor are similar in body size, setation patterns on the naupliar appendages, labrum, dorsal setae-pores, frontal horns, cyprid carapace, fronto-lateral gland pores, and lattice organs. Numbers of peculiarities were observed on the gnathobases of the antennae and mandible throughout the naupliar life-cycle. The setation pattern on the naupliar appendages are classified based on the segmentation on the naupliar appendages. The nauplius VI of both species undergoes a conspicuous change before metamorphosis into cyprid stage. The cyprid structures begin to form and modify beneath the naupliar body towards the end of stage VI. This study emphasises the importance of the pedunculate barnacle larval developmental studies not only to comprehend the larval morphological evolution but also to fill in the gaps in understanding the modification of the naupliar structures to adapt into the cyprid life-style.